Genomic organization and comparative chromosome mapping of the U1 snRNA gene in cichlid fish, with an emphasis in Oreochromis niloticus - Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Valente, G. T. [UNESP]; Nakajima, R. T. [UNESP]; Martins, C. [UNESP] (Springer, 2012)
To better understand genomic and chromosomal organization and evolutionary patterns of the U1 snRNA gene in cichlid fish, the gene was cytogenetically mapped and comparatively analyzed in 19 species belonging to several clades of the group. Moreover, the distribution and organization of U1 snRNA gene was analyzed in the Oreochromis niloticus genome. The results indicated high conservation of one chromosomal cluster of U1 snRNA in the African, Asian, and South American species, with few variations in the chromosomal position of the clusters in the South American species. The genomic analysis of U1 revealed a distinct scenario from that observed under the cytogenetic mapping. An enrichment of the U1 gene on linkage group (LG) 14 was observed that did not correspond to the same chromosome that harbors the U1 cluster identified by cytogenetic mapping. Moreover, it was revealed that the presence of several distinct transposable elements in the U1 gene flanking regions could be involved in the spreading of this sequence, but the generation of new, large snRNA clusters (detectable by fluorescent in situ hybridization, FISH) is apparently hampered. These results contribute to the understanding of multigene families' evolution and reinforce the utility of integrative analysis and the use of cytogenetic and bioinformatic methods to address the genomic and chromosomal evolutionary patterns of repeated DNAs among vertebrates. Moreover, the U1 gene represents a useful new chromosomal marker for cytogenetic studies.
Keywords: chromosomal evolution; cytogenetic; FISH; genome; multigene family; Teleostei; Cichlidae